Ultra-compact 122GHz Radar Sensor for Autonomous Aircrafts - Nava, Federico; Scheytt, Christoph; Zwick, Thomas; Pauli, Mario; Goettel, B.; Winkler, Wolfgang (3rd International Conference on System-Integrated Intelligence)
In this paper a prototype of an ultra-compact continuous-wave (CW) and frequency-modulated continuous-wave (FMCW) radar system using a highly-integrated radar chip and in-package antennas will be presented. An introduction will be given on the concept of antenna integration for millimeter-wave radar and the advantages of such systems. The radar then will be described in its main components, a 122 GHz Integrated Circuit including in-package antennas as well as the acquisition and processing system realized using flexible printed circuit board (FLEX PCB) technology. Furthermore initial measurements of the radar system will be presented and explained.

Some reflections on electromagnetic force in matter - Böcker, Joachim (2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Local demand response and load planning system for intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim (2015 International Conference on Renewable Energy Research and Applications (ICRERA))

Integration of home photovoltaic generation into electricity tariff for load optimization - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 4th International Istanbul Smart Grid Congress and Fair (ICSG))

Local grid load coordination for load-shiftable domestic appliances in a variable-tariff environment - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Supervisional load optimization for households with intelligent domestic appliances - Stille, Karl Stephan Christian; Böcker, Joachim; Fröhleke, Norbert; Bettentrup, Ralf; Kaiser, Ingo (2016 10th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG))

The Interplay between Logic and Metaphysics - Ficara, Elena (Hegel and Metaphysics)

Two in One - Ficara, Elena (The Power of Distributed Knowledge)

Real-time capable model predictive control of permanent magnet synchronous motors using particle swarm optimisation - Wallscheid, Oliver; Ammann, Ulrich; Böcker, Joachim (PCIM Europe 2016; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Quantile treatment effects of job loss on health - Schiele, Valentin; Schmitz, Hendrik (Journal of Health Economics)

Public reporting and the quality of care of German nursing homes - Herr, Annika; Nguyen, Thu-Van; Schmitz, Hendrik (Health Policy)

Determinants of regional variation in health expenditures in Germany - Göpffarth, Dirk; Kopetsch, Thomas; Schmitz, Hendrik (Health economics)

Health shocks and risk aversion - Decker, Simon; Schmitz, Hendrik (Journal of Health Economics)

2D analytical model for estimation of eddy current loss in the magnets of IPM machines considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Voltage controller for flux weakening operation of interior permanent magnet synchronous motor in automotive traction applications - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2015 IEEE International Electric Machines & Drives Conference (IEMDC))

Analysis of eddy current losses in the stator windings of IPM machines in electric and hybrid electric vehicle applications - Paradkar, M.; Böcker, Joachim (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of quarter-wave with half-wave symmetrical pulse patterns applied in electrical high-speed drives - Peter, K.; Böcker, Joachim; Mink, F.; Beineke, S. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Comparison of Optimized Pulse Patterns with Direct Model Predictive Control Using Co-Simulation - Schulte, C.; Peter, K.; Böcker, Joachim; Leuer, M. (8th IET International Conference on Power Electronics, Machines and Drives (PEMD 2016))

Inverter loss management for an electrical high-speed drive system - Peter, Klaus; Hanke, Soren; Mink, Fabian; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))

Sensitivity analysis on production tolerances for electric drive systems in automotive application - Ott, Markus; Böcker, Joachim (2016 18th European Conference on Power Electronics and Applications (EPE'16 ECCE Europe))